2017
DOI: 10.3389/fphys.2017.01079
|View full text |Cite
|
Sign up to set email alerts
|

Acute Heat Stress Alters the Expression of Orexin System in Quail Muscle

Abstract: Accumulating evidences indicate that the hypothalamic neuropeptide orexins or hypocretins are involved in stress-induced responses in mammals. Recently, we found that orexin is expressed and secreted from avian muscle cells, however its regulation is still unknown. In this study, we investigated the effect of heat and oxidative stress, the most challenging stressors in poultry production, on the expression of orexin system in quail muscle tissues and myoblast cell lines. Four week-old genetically selected susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
(70 reference statements)
2
18
0
Order By: Relevance
“…We speculated that this decrease in feeding may be related to the impaired mobility in hens and stress induced by keel fractures. Some researchers have reported that negative emotions, heat, and oxidative stress downregulate the expression of avian orexin and orexin receptors genes, which may inhibite the feeding motivation ( Greene et al., 2016 , Nguyen et al., 2017 ). Likewise, our previous study has found that keel fracture causes stress response and inhibits the gene expression of orexin and its receptors ( Wei et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that this decrease in feeding may be related to the impaired mobility in hens and stress induced by keel fractures. Some researchers have reported that negative emotions, heat, and oxidative stress downregulate the expression of avian orexin and orexin receptors genes, which may inhibite the feeding motivation ( Greene et al., 2016 , Nguyen et al., 2017 ). Likewise, our previous study has found that keel fracture causes stress response and inhibits the gene expression of orexin and its receptors ( Wei et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high metabolic activity and lack of sweat glands, modern broilers are particularly sensitive to heat stress. The strong adverse effects of heat stress on growth, feed intake, feed efficiency, meat yield and quality, welfare, and mortality are well documented in broilers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Emerging evidence indicates that heat stress alters also the gut morphometry (lower crypt depth, mucous area, and villus height) which in turn affect nutrient absorption (21).…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in blood (oxygen) and energy supplies result in stress and damage to many internal organs. The strong adverse effects of heat stress on poultry production, welfare, meat quality, and mortalities are well-documented and elegantly reviewed elsewhere (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%